Transhumanism and One Health - Jakob Zinsstag; Andrea Kaiser Grolimund; Engin Tulay; Reinhold Bernhardt (CABI, 2024)
Abstract In this article, we draw on an interdisciplinary seminar at the University of Basel in the spring semester 2023. The seminar firstly discussed technical transhumanism between improving human lives through technological innovation and breathtaking advances in artificial intelligence (AI). Secondly, integrative approaches to health such as One Health have a transhumanist dimension, meaning that the interaction of human and animal health contributes to human health and development. As technological and biological dimensions of transhumanism raise philosophical, anthropological and ethical questions, we ask what is specifically human and what kind of future human-technology interactions is societally acceptable. With the rapid recent development of AI, questions arise about algorithms taking over human intellectual functions. Transhumanism can be described as a current of a posthumanist turn that generally asks where the limits of the human body and also of human existence lie. From an anthropological point of view a controversial discussion is held 'beyond the human' about blurring of the boundaries between humans, animals and nature. The One Health approach demands that animals should not suffer in place of humans and that the health of humans, animals, plants and the environment must be promoted simultaneously. This places the One Health approach in a tension and dilemma between conflicting ethical and purely human demands for the protection and welfare of animals, as well as the legitimate demands for animal food and sheer survival in many areas of the world. A biological transhumanism certainly has less of a claim to surpass specifically human performance and thus stands less or not at all in the more gnostic technological current of technical transhumanism, which replaces human labour and suddenly achieves the ability to turn against humans. One Health impact statement Integrative approaches to health such as One Health have a transhumanist dimension, meaning that the interaction of human and animal health contributes to human health and development. The One Health approach demands that animals should not suffer in place of humans and that the health of humans, animals, plants and the environment must be promoted simultaneously. This places the One Health approach in a tension and dilemma between conflicting ethical and purely human demands for the protection and welfare of animals, as well as the legitimate demands for animal food and sheer survival in many areas of the world. Because of the high variability of the culturally-religiously shaped human-animal-environment relationship, such a transdisciplinary, participatory consensus would need to be contextually adapted, that is, to geographically, culturally-religiously distinct situations.Keywords: Transhumanism, Technical, Biological, One Health, Anthropology, Ontology, Ethics